Effects of ranibizumab on microvasculature, oxidative stress and recurrence in primary pterygium surgery - Yap, Jin Yi; Tai, Evelyn Li Min; Yee, Cheng Kueh; Salzihan Salleh; Mohtar Ibrahim (Springer Nature, 2025)
Purpose To evaluate the effects of pre-operative ranibizumab injection on microvascular density (MVD), 8-hydroxyguanosine (8-OHdG) and recurrence after surgical excision of primary pterygium. Method This was a prospective cohort interventional study involving 52 patients with primary pterygium divided equally into control and intervention groups. The intervention group received 0.5 mg ranibizumab two weeks prior to pterygium excision surgery. All participants had pterygium excision with autologous conjunctival graft under local anaesthesia. Excised pterygium tissues were evaluated for MVD and 8-OHdG. Each participant was monitored for recurrence up to 2 years after intervention. Pearson chi-square and Fisher exact tests were used to examine the differences between both groups.